Parasitoid impairment on the galling Lopesia sp. activity reflects on the cytological and histochemical profiles of the globoid bivalve-shaped gall on Mimosa gemmulata - Costa, Elaine C.; Oliveira, Denis C.; Isaias, Rosy M. S. (Protoplasma, 2022)
Gall cytological and histochemical features established by the constant feeding activity of the associated gall inducer may be changed due to the attack of parasitoids. We accessed two tri-trophic systems involving the globoid bivalve-shaped gall on Mimosa gemmulata Barneby (Fabaceae) and its galling undescribed species of Lopesia (Diptera: Cecidomyiidae), which may be ectoparasitized by Torymus sp. (Hymenoptera: Torymidae) or endoparasitized by a polyembryonic Platygastridae (Hymenoptera), as models of study. The ectoparasitoid species paralyzes and kills Lopesia sp. larva, which stops the feeding stimuli, while the endoparasitoid larvae feed in Lopesia sp. larva body and keep it alive for a certain time. Our hypothesis is that the time lapse of Lopesia sp. feeding impairment by the two parasitoids will cause distinct cytological and histochemical responses in the ecto- and endoparasitized galls compared to the non-parasitized condition. In both parasitoidism cases, the impairment of the feeding activity of the galling Lopesia sp. directs the common storage and nutritive cells toward a similar process of induced cell death, involving cell collapse and loss of membrane integrity. The cell metabolism is maintained mainly by mitochondria, and by the translocation of lipids from the common storage tissue, via plasmodesmata, through the living sclereids of the mechanical zone toward the nutritive tissue. Accordingly, the parasitoid impairment on the feeding activity of Lopesia sp. larvae causes precocious senescence, but similar cytological alterations, and no impact over the histochemical profiles, regarding lipids, reactive oxygen species, and secondary metabolites, which support gall metabolism along the parasitoid cycles.